External Fixation: Daily versus Weekly Pin Site Care (Medical Forum Monthly, 2024)
Objective: To determine whether there were any differences in the frequency and severity of pin site infections by performing pin site care daily or once a weekStudy Design: cross sectional descriptive study.Place and Duration of Study: This study was carried out at Department of Orthopaedics and Traumatology, Khyber Teaching Hospital, Peshawar during the period from Dec 2011 to Jun 2013.Materials and Methods: This study included 96 patients who were selected by convenient (non probability) sampling technique. Patients were divided into two groups.Results: The mean infection rate during the study in group 1 was grade I in 16% and grade II in 7%, grade III in1% versus grade I in 12% and grade II in 5%, grade III in 5% in group 2. No grade IV–VI infections were noted.Antibiotics were prescribed for a mean of 60 days (SD 15) in group 1 and 45 days (SD 30) in group 2. The relative risk (RR) of positive cultures at the proximal pin sites was 1.5 (95% CI 1.2–1.9). No difference was found between the groups.Conclusion: No differences between daily and weekly pin site care were observed as regards the severity of infections, frequency of infection rate, of positive cultures, except in week 6, and in use of antibiotics or analgesics.